Blue Economy and Green Economy: Ecocritical Study of Kompas Short Stories Collection Keluarga Kudus - Rosita Sofyaningrum; Ahmad Irham Maulana; Karina Sistiyaningrum; Feri Alfian (SUAR BETANG, 2023)
This study examines environmental damage in literary works that affects people's lives. This study aims to describe the difficulty of surviving due to environmental damage. Enviromental damage can be overcome by blue economy and green economy,especially in economic improvement and environmental protection. The data sources used in this research are four short stories related to the environment. By using a qualitative descriptive method, the following things were found. The description of environmental damage is depicted through narrative quotes and dialogues from the characters:(1) the difficulty of finding the three-colored bahar root as a drug, (2) the scarcity of clean water sources due to pollution and construction building, (3) the decline in crop yields due to changes in weather, and (4) the ancestral lands no longer able to give life. Second, the survival difficulties of the characters which are described through the narrative quotes and dialogues of the characters. Descriptions of difficulties in survival are (1) difficulties to find food to sustain life in coastal communities, (2) difficulties to find food to the point of sacrificing lives, (3) difficulties to find clean water sources, (4) rubber plantations that are unable to support farmers and their families, (5) the occurrence of crime, and (6) migration some people for a better life. Third, the importance of green economy and blue economy in overcoming the life difficulties of the characters in short stories and reducing environmental damage.AbstrakPenelitian ini mengkaji kerusakan lingkungan dalam karya sastra yang memengaruhi kehidupan masyarakat. Penelitian ini bertujuan mendeskripsikan sulitnya bertahan hidup akibat kerusakan lingkungan. Kerusakan lingkungan dapat diatasi dengan blue economy dan green economy,khususnya dalam peningkatan ekonomi dan pelindungan lingkungan. Sumber data yang digunakan dalam penelitian adalah empat cerpen yang berkaitan dengan lingkungan. Dengan menggunakan metode deskriptif kualitatif, ditemukan hal-hal berikut. Pertama, gambaran kerusakan lingkungan digambarkan melalui kutipan narasi dan dialog para tokoh. Gambaran kerusakan lingkungan meliputi (1) sulitnya menemukan akar bahar tiga warna sebagai obat, (2) langkanya sumber air bersih akibat pencemaran dan pembangunan gedung, (3) menurunnya hasil panen akibat adanya perubahan cuaca, dan (4) tanah leluhur yang sudah tidak mampu memberikan kehidupan. Kedua, kesulitan bertahan hidup para tokoh yang digambarkan melalui kutipan narasi dan dialognya. Gambaran kesulitan bertahan hidup meliputi (1) sulit mencari makanan untuk menyambung hidup masyarakat pesisir, (2) sulitnya mencari makan hingga mengorbankan nyawa, (3) sulitnya menemukan sumber air bersih, (4) perkebunan karet yang tidak mampu menghidupi petani dan keluarganya, (5) terjadinya kriminalitas, dan (6) perantauan beberapa orang untuk mencari kehidupan yang lebih baik. Ketiga, pentingnya green economy dan blue economy dalam mengatasi kesulitan hidup tokoh dalam cerpen dan mengurangi kerusakan lingkungan.